Labour mobility in the euro area: cure or curse for imbalances? - auf dem Brinke, Anna; Dittrich, Paul-Jasper (Gütersloh, 2016)
"The euro area has to address its imbalances and instability. Labour mobility in a currency union can be both a curse or a cure in this context. When job seekers move from areas with high employment to regions with many vacancies, they act effectively as shock absorbers. However, when young and better educated individuals move from structurally weak regions to dynamic ones, they can contribute to imbalances."